1998
DOI: 10.1016/s0584-8547(98)00076-7
|View full text |Cite
|
Sign up to set email alerts
|

Microscopical speciation analysis with laser microprobe mass spectrometry and static secondary ion mass spectrometry

Abstract: This paper presents a set of data which compares the potential and limitations of laser microprobe mass spectrometry (TOF-LMMS and FT-LMMS) and static secondary ion mass spectrometry (S-SIMS) for inorganic speciation at a microscopical level. In general LMMS yields prominent signals of adduct ions consisting of the intact molecule combined with a stable ion, which allows a direct identification of the analyte. S-SIMS also yields abundant diagnostic signals to specify the molecular composition. However, adduct … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
25
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(31 citation statements)
references
References 30 publications
5
25
1
Order By: Relevance
“…97, 350.91, 516.82, and 682.71, that are present in negative mode spectra of thenardite with and without glycine present (Figure 1). The high m/z peaks observed are different from those observed by Van Vaeck et al (1998) for Na 2 SO 4 using a laser wavelength of 266 nm. In addition to the difference in laser wavelength, there are differences in the FTICR-MS parameters used to obtain the spectra that may be important because Van Vaeck et al (1998) demonstrated that the production of higher m/z cluster ions is dependent on gas-phase reactions.…”
Section: Glycine and Thenarditecontrasting
confidence: 86%
“…97, 350.91, 516.82, and 682.71, that are present in negative mode spectra of thenardite with and without glycine present (Figure 1). The high m/z peaks observed are different from those observed by Van Vaeck et al (1998) for Na 2 SO 4 using a laser wavelength of 266 nm. In addition to the difference in laser wavelength, there are differences in the FTICR-MS parameters used to obtain the spectra that may be important because Van Vaeck et al (1998) demonstrated that the production of higher m/z cluster ions is dependent on gas-phase reactions.…”
Section: Glycine and Thenarditecontrasting
confidence: 86%
“…These behavioral attributes have motivated research into surface speciation of Cr-bearing surfaces, with the intent of correlating the explicit chemical form of the metal with transport and toxicity. Substantial research on Cr speciation has utilized desorption ionization mass spectrometry, either laser desorption mass spectrometry [4 -16] or secondary ion mass spectrometry [14,[17][18][19][20]. These studies showed that indeed Cr surface speciation could be correlated with the mass spectral fingerprint generated by the desorption ionization studies.…”
mentioning
confidence: 99%
“…Abundances of oxides detected in present study could not be reduced by applying higher laser irradiances. Other laser ablation studies show as well that the formation of clusters and oxides is not avoidable and results from variety of chemical processes which can take place in plasma [41][42][43][44][45].…”
Section: Allendementioning
confidence: 99%